El diálogo judeo-cristiano en el "Scrutinium Scripturarum" de Pablo de Santa María - Tábet, Michelangelo (Annali di storia dell'esegesi, 1999)
In the first part of Scrutinium Scripturarum an imaginary dialogue is developed between a Jew and a Christian (Paul himself before and after his conversion), in which each party brings forth arguments based on a common belief: faith in Scripture and a great respect for the authorities of the Jewish exegetical tradition. In our day the work of Paul has much to teach us. Its value lies not in that which is transitory in it - a type of exegesis rooted in categories which today have been partly superseded but rather in the way in which it brings about an inter-religious dialogue, which ultimately is nothing other than a dialogue with one's own conscience. For the Christian, certainly, the work of the Bishop of Burgos is a call to give full value to the Jewish tradition, to which he must feel himself to be profoundly tied and to which he is indebted for a certain understanding of the sacred text.